Preparation and Evaluation of Hydrogel Formulation Containing Ocimum sanctum Leaves Extract for Anti-inflammatory Activity - Jain, Dr. Alok Pal (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the present study was to evaluate the anti-inflammatory effect of Ocimum sanctum leaves in the formulation of hydrogel using different types of animal models. Materials and Methods: Ethanolic extract of O. sanctum leaves was fractionated with methanol to get methanolic fraction. Methanolic fraction (1%vw/w) was used for hydrogel formulation with different combinations of Carbopol 940 and sodium CMC. Prepared hydrogel was characterized for optimum physical characters, pH, spreadability, homogeneity, viscosity, release profile, and irritation effect. Optimized hydrogel was evaluated for anti-inflammatory effect using xylene-induced, croton oil-induced ear edema, and cotton pellet-induced granuloma model in animals. Effect was monitored by the measurement of percent inhibition, nitric oxide (NO), and myeloperoxidase (MPO) levels in mice ears after acute inflammation induced by croton oil. Results and Discussion: Physical evaluation confirmed that the color of the prepared hydrogels was brownish and appearance was homogeneous and smooth on application. All other evaluation parameters, for example, pH, viscosity, spreadability, and consistency were found suitable in F3 hydrogel formulation combination. Hence, the optimize composition of F3 formulation was observed as 1.5 g of Carbopol 940 and 1% of sodium CMC. Percent inhibition of edema in xylene-induced ear edema in mice was found comparable to standard group of treatment (65.59%). In the present study, result indicates that prepared hydrogel OSMFH possesses inhibitory effects against acute inflammation. The results showing the ability of croton oil to induce neutrophil influx into mice ear tissue. This may be reduced by treatment with extract hydrogels, as well as Voltaren Emulgel, reduced significantly (P < 0.01) the MPO levels and NO levels in mice ears. Conclusion: The methanol extracts were exhibits its anti-inflammatory action significantly may be due to the presence of flavonoids in O. sanctum leaves.